Understanding the extent of phenotypic variability in accessions of Paspalum urvillei Steud. From the USDA NPGS - Ferreira, Juliano Lino; Gwinner, Raoni; Ferreira, Leila Maria; Ferronato, Jéferson; Leite, Leandro Gonçalves; Ferreira, Kátia Graciele Gonçalves; Silva, Júlio César Rodrigues Lopes [UNESP]; dos Santos, Luís Paulo; Silva, Alisson Wilians Teixeira (Editora Letra1, 2020)
The objective of this study was to investigate the phenotypic variability in Paspalum urvillei Steud. related to twelve zootechnical traits to better understand the diversity of 41 accessions from the USDA GRIN platform from seven countries. First, we performed a structure inference based on the phenotypic data, identifying two structure groups, and the majority of Brazilian accessions belonged to the first group. Then, we performed principal component analysis and principal coordinate analysis, making Violin plots for each trait within each structure group. Next, we performed spatial clustering of the accessions and utilized an unweighted pair group method with arithmetic mean clustering. In brief, the Brazilian P. urvillei breeding programs may be successful by importing USDA germplasm resources from the second phenotypic structure group.
Entendendo a extensão da variabilidade fenotípica em acessos de Paspalum urvillei Steud. do banco de germoplasma do USDA NPGS
Keywords: Cluster analysis; Forage; Germplasm bank